2014
DOI: 10.1016/s1001-9294(14)60023-7
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Animal Research on Electro-acupuncture Treatment for Depression

Abstract: This paper summarized the Chinese literatures in the previous 5 years about the pre-clinical animal researches on the application of electro-acupuncture (EA) treatment for depression, searched in China National Knowledge Infrastructure (CNKI). The efficiency of EA treatment for depression and the mechanism of it were discussed, to shed light on new ideas and new fronts for the further research on depression in clinical or pre-clinical fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Furthermore, since animals likely do not understand the difference between true vs sham therapies, we can infer that they are not likely to exhibit a placebo response. [71][72][73][74][75][76][77][78][79][80][81] Some argue that acupuncture is no better than placebo since a few human studies showed no significant difference between sham needling and true acupuncture-ignoring the effects of needle insertion itself. 82 Nevertheless, blinding attempts with non-penetrating shams are possible in humans.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Furthermore, since animals likely do not understand the difference between true vs sham therapies, we can infer that they are not likely to exhibit a placebo response. [71][72][73][74][75][76][77][78][79][80][81] Some argue that acupuncture is no better than placebo since a few human studies showed no significant difference between sham needling and true acupuncture-ignoring the effects of needle insertion itself. 82 Nevertheless, blinding attempts with non-penetrating shams are possible in humans.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%